BARIUM LEVELS IN THE PROSTATE OF THE NORMAL HUMAN: A REVIEW - Zaichick, Vladimir (Universal Journal of Pharmaceutical Research, 2021)
Knowledge of the etiology and pathogenesis of most prostate malfunctions and pathologies is very limited. Despite advances in medicine, the differential diagnosis of benign hypertrophic and carcinogenic prostate has steadily increased in complexity and controversy. It has been suggested that the prostate barium level (Ba) may help solve these problems related to prostate disorders, especially as an indicator of prostate cancer risk, as an elevated Ba level in the prostate may be a sign of prostate cancer in the future. These suggestions promoted more detailed studies of the Ba level in the prostate of healthy men. In present review we analyze data published concerning Ba prostatic levels in healthy persons. In all 2194 items in the literature of the years dating back to 1921 were identified in the following databases: PubMed, Scopus, Web of Science, the Cochrane Library, ELSEVIER-EMBASE and Google. This data was subject to an analysis employing both the “range” and “median” of means. In this way the disparate nature of published Ba content of normal prostates was evaluated. Of the articles examined, 20 were selected for objective analysis of data from 1049 healthy subjects. The contents of prostatic Ba (on a wet mass basis) spanned the interval from 0.021 mg/kg to 222 mg/kg with 0.26 mg/kg as median for their means. The data included a wide range of values ​​and the samples were small, hence it is advisable that further studies with strong quality control of results be performed. Peer Review History: Received 6 December 2020; Revised 8 January 2021; Accepted 11 February; Available online 15 March 2021 Academic Editor: Prof. Dr. Gorkem Dulger , Duzce University, Turkey, gorkemdulger@yandex.com Reviewer(s) detail: Dr. U. S. Mahadeva Rao , Universiti Sultan Zainal Abidin, Terengganu Malaysia, raousm@gmail.com Prof. Dr. Hassan A.H. Al-Shamahy , Sana'a University, Yemen, shmahe@yemen.net.ye